Effect Of Perceived Desirability, Usefullness, Accessibility To Decision Through The Interest Of Choosing Politeknic Educational Study In East Java - Kunto Eko Susilo; Beni Agus Setiono; Tri Andjarwati; Endah Budiarti (Journal of Indonesian Science Economic Research, 2019)
This study aims to analyze the influence of Perceived Desirability, Usefullness, Accessibility To Decision Through Interest Choosing Polytechnic Education Studies In East Java. With interest in choosing (Intention to Choose) as intervening variable. The method used in this research is the survey method conducted on Polytechnic students in East Java. The sample in this study were 395 respondents. The data used in this study is the primary data sourced from the questionnaire. Data analysis and hypothesis test in this research using Structural Equation Model (SEM). The results showed that each variable Perceived Desirability, Usefullness, Accessibility significantly influence the decision through the interest in choosing Polytechnic Education Studies in East Java. Perceived Accessibility has no significant effect on the decision through the interest in choosing Polytechnic Education Studies in East Java.